HUBUNGAN ANTARA BUDAYA ORGANISASI DAN KEPEMIMPINAN TRANSFORMASIONAL DENGAN KINERJA PEGAWAI (Studi Kasus Pada Pegawai UPT BPPSDMP Kementerian Pertanian Di Bogor) - Doni Maryanto; Mohammad Entang; Widodo Sunaryo (MAGMA : JURNAL MAGISTER MANAJEMEN, 2021)
The purpose of this study is to determine the correlation between organizational culture and transformational leadership together with the performance of employees at the UPT BPPSDMP Ministry of Agriculture in Bogor. The population in this study was the number of employees of the Official Government (ASN) with general functional positions as many 140 people. With a total sample taken amounted to 104 with Slovin formula. The results showed (1) there is a positive and significant correlation between organizational culture and employee performance with a correlation coefficient (r) of 0,848. The contribution of organizational culture (X₁) to employee performance (Y) is calculated based on the determination coefficient value, it is known that the value of R Square = 0,719, This means that organizational culture (X₁) forms a contribution of 71,9% to employee performance (Y). (2) there is a positive and significant correlation between transformational leadership and employee performance with a correlation coefficient (r) of 0.747. Transformational leadership contribution (X₂) to employee performance (Y) is calculated based on the determination coefficient value of R Square = 0,558, This means that transformational leadership (X₂) forms a contribution of 55,8% to employee performance (Y). (3) there is a positive and significant correlation between organizational culture and transformational leadership together with employee performance with the value of the correlation coefficient (r) of 0,853. The contribution of organizational culture (X₁) and transformational leadership (X₂) together on employee performance (Y) is calculated based on the determination coefficient value Adjusted R Square (R²) = 0,727, this shows that 72,7% employee performance is influenced by organizational culture and transformational leadership.